Impact of Emotional Intelligence on Nurses’ Burnout Level and Job Satisfaction - Saleem, Bushra; Ali, Rubab; Noreen, Saira (Biological and Clinical Sciences Research Journal, 2025)
Burnout among nurses is a critical occupational health concern that adversely affects patient care quality and workforce retention. Emotional intelligence (EI) is increasingly recognized as a key psychological factor influencing stress resilience and job satisfaction in healthcare professionals. Objective: To evaluate the impact of emotional intelligence on nurses' burnout levels and job satisfaction. Methodology: Nurses working in the Nursing Department of Sheikh Zayed Hospital, RYK, were cross-sectionally analyzed from June 2024 to June 2025. A total of 100 nurses working in the hospital for 1 year or more were included in the study. Personal data of nurses, including gender and marital status, were noted. Emotional intelligence was evaluated by the translated version of the 28-item questionnaire designed by Bradbury and Graves. Burnout was assessed using a 22-item questionnaire designed by Maslach and Jackson. Job satisfaction was determined by a 39-item questionnaire designed by Visoki and Chrome on five dimensions: job component, promotion, supervisor, payment, and colleague. Results: A significant F ratio of 44.818 was recorded between burnout and emotional intelligence. The R2 value showed that a 0.09% change in burnout level can be predicted by emotional intelligence. There was also a significant F ratio of 772.797 between job satisfaction and relationship management, a component of emotional intelligence. A 0.61% change in job satisfaction could be predicted by relationship management. Burnout was significantly associated with all components of emotional intelligence: relationship management (0.363), social awareness (0.213), self-management (0.148), and self-awareness (0.147). Conclusion: Emotional intelligence significantly impacts burnout levels in nurses with a high EI, reducing burnout.